New frontiers in mining complex patterns : third International Workshop, NFMCP 2014, held in conjunction with ECML-PKDD 2014, Nancy, France, September 19, 2014, Revised selected papers /: third International Workshop, NFMCP 2014, held in conjunction with ECML-PKDD 2014, Nancy, France, September 19, 2014, Revised selected papers. (2015) - Unknown
No abstract available